Produtividade e nutrição do abacaxizeiro adubado com lodo de esgoto - Geraldo Ribeiro Zuba Junio (2019)
The expansion of basic services of sanitation of Brazilian municipalities has generated a large amount of sewage sludge, which discard is made mainly in landfills. Although of it needs some special care in its handling, the sewage sludge presents enormous potential for use as agricultural fertilizer. However, the use of sewage sludge in agriculture can increase the levels of heavy metals in the soil, compromising their sustainable use. The pineapple, due to its characteristics, is a crop suitable for fertilization with sewage sludge, according to CONAMA Resolution nº 375, of August 29, 2006. Considering the enormous importance of this crop for Brazil, the use of sewage sludge in the cultivation of this species can constitute itself in important fertilizer economy, besides the adequate destination of this residue. In view of the above, the main objective ofthis work was to evaluate the agronomic characteristics of the pineapple and the analysis of the risk of contamination of the plant and three orders of soil with heavy metals after the application of stabilized sewage sludge in greenhouse. The study was delineated in a randomized complete block with three replications, with a 7 x 3 factorial arrangement, corresponding to seven fertilization treatments: soil without fertilization, chemical fertilization, fertilization with composted sludge sewage, fertilization with vermicompost sewage sludge, fertilization with solarized sewage sludge, fertilization as sewage sludge dried in a Bruthus-Albrecht rotary sludge dryer and fertilization with limed sludgesewage, combined with three orders of soils: Cambisol, Nitisol and Acrisol. Fertilization with sewage sludge promoted little variation in soil fertility, plant nutrition and pineapple production between the Acrisol, Cambisol and Nitisol. In addition, these variables were, in general, similar between the different types of sewage sludge used in fertilization and the chemical fertilization, indicating the potential use of these organic fertilizers in pineapple cultivation. The fertilization with composted, vermicompost and solarized sewage sludge provided higherlevels of Pb, As, Zn in leaf D and in pineapple fruit.